Ta‘līm “al-‘Arabiyyah li-al-Nāsyi’īn” li-al-Juz’ al-Awwal bi-Istikhdām Ṭarīqah al-Qaṣṣah fī al-Ma‘had al-Islāmī “Dār al-Falāḥ al-Khāmis Cukir Jombang” - Shomadiyah, Wardatus; Qodir, Abdul (Program Studi Pendidikan Bahasa Arab, 2023)
This study examines the learning of the Kitab al arobiyatun lin nasyiin juz 1 using the storytelling method at the Darul Falah 5 Cukir Islamic Boarding School, Diwek Jombang. The formulation of the problem in this study is 1) how is the learning of the Kitab al arobiyatun lin nasyiin juz 1using the storytelling in the Darul Falah 5 Cukir Islamic Boarding School in Jombang? 2) How is the study of Kitab al arobiyatun lin nasyiin juz 1 using the storytelling method at the Darul Falah 5 Cukir Islamic Boarding School, Diwek Jombang? 3) what are the advantages and disadvantages of learning Kitab al arobiyatun lin nasyiin juz 1 using the storytelling method at the Darul Falah Islamic boarding school 5 Cukir Diwek Jombang. This research method uses descriptive qualitative methods, data collection from this research is observation, interviews, and documentation then analyzed into a descriptive qualitative method. data that can be presented according to research results. The results of the research examine the learning of the Kitab al arobiyatun lin nasyiin using the storytelling method at the Darul Falah Islamic boarding school 5 Cukir Diwek Jombang, namely the learning of the Kitab al arobiyatun linnasyiin is learning that teaches material and exercises about Arabic. This book has several volumes including volumes 1 to 6. Volumes of itab al arobiyatun linnasyiin are taught according to the students being taught, from basic knowledge of Arabic to the book of al arobiyatun linnasyiin volume 6. learning the book al arobiyatun linnasyiin juz 1 at the Darul Falah 5 Islamic boarding school using the method storytelling The learning system that is carried out is to first provide the existing material then students are allowed to ask which material is not clear and ask for meanings that are not yet known then the teacher invites students to take the essence or material that was understood using Arabic after that the teacher appoints several children to come forward in front of the class to present the results and the other assignments are collected to be corrected by the teacher. learning the Kitab al arobiyatun linnasyiin using juz 1 the storytelling method at the Darul Falah 5 Islamic boarding school has several advantages, namely it can be followed by a large number of students, the teacher controls the class, the implementation is easy, trains students to recognize new vocabulary quickly, understands material with a long period of time and practice writing and speaking skills. The storytelling method has drawbacks, namely the evaluation of the learning process is difficult to control because there are no clear achievement points and this method takes a lot of time while learning only lasts for 1 hour so that students are less focused on stories made in haste.